A novel HIF-1α-integrin-linked kinase regulatory loop that facilitates hypoxia-induced HIF-1α expression and epithelial-mesenchymal transition in cancer cells - Chou, Chih-Chien (Oncotarget, 2015)
Here, we described a novel regulatory feedback loop in which hypoxia induces integrin-linked kinase (ILK) expression through a HIF-1α-dependent mechanism and ILK, in turn, stimulates HIF-1α expression through cell type- and cell context-dependent pathways. HIF-1α increased ILK via transcriptional activation. ILK increased HIF-1α levels by promoting mTOR-mediated translation in PC-3 and MCF-7 cells, and by blocking GSK3β-mediated degradation in LNCaP cells, consistent with the cell line-/cellular context-specific functions of ILK as a Ser473-Akt kinase. We show that ILK can account for the effects of hypoxia on Akt, mTOR, and GSK3β phosphorylation. Also, ILK can de-repress HIF-1α signaling through the YB-1-mediated inhibition of Foxo3a expression. In concert with HIF-1α, these downstream effectors promote epithelial-mesenchymal transition (EMT) through modulation of Snail and Zeb1. Thus, the ILK-HIF-1α regulatory loop could underlie the maintenance of high HIF-1α expression levels and the promotion of EMT under hypoxic conditions. Finally, we show that the small-molecule ILK inhibitor T315 can disrupt this regulatory loop in vivo and suppress xenograft tumor growth, thereby providing proof-of-concept that targeting ILK represents an effective strategy to block HIF-1α expression and aggressive phenotype in cancer cells.